(untitled) (Asian Journal of Medical and Biological Research, 2021)
In Bangladesh, Diarrhea occurs in goats of any age and is responsible for poor growth in kids and a significant loss of production both through morbidity and mortality. The study was undertaken to determine the clinical prevalence of diarrheal diseases of goats with concurrent blood profile. A total of 1,007 goats were examined which were brought for treatment in the Upazilla Veterinary Hospital, Biral, Dinajpur. Among them 149 goats were found clinically affected by diarrhea and the overall prevalence of diarrheal disease in goats was 14.80%. A total of 402 male and 605 female goats were examined and their diarrheal prevalence were 14.17%, 15.15%, respectively. The Prevalence in Jamnapari goat (18.80%) was signicantly (P<0.01) higher than in Black Bengal goats (14.26%). The prevalence (59.52%) in suckler (below 3 months) was much significantly (P<0.001) higher than in young (12.47%) and adults (13.42%). Higher prevalence was found due to parasitic infection (38.25%) with a declining order in PPR (30.20%), overfeeding (24.16%) and poisoning (7.30%). The leukocyte number significantly (P<0.001) higher in goats affected by diarrhea whereas TEC, PCV, Hb and Erythrocyte Indices were in normal ranges. From this study, it can be concluded that suckler, female goats and Jamnapari goats are more susceptible to diarrhea than adult, male goats and Black Bengal goats. Asian J. Med. Biol. Res. March 2021, 7(1): 6-11